2-D switched-beam leaky-wave antenna system using butler matrix - Lu, Chongqing (Nanyang Technological University, 2021)
Millimeter-wave (mmW) communication has been considered as one promising technology for the fifth-generation (5G) communication systems. Beam scanning/beam steering antenna systems are demanded recent years due to advanced wireless system at millimeter wave for connectivity and 5G applications. Generally, the composite left-right-handed leaky-wave antennas have one direction beam scanning. The Butler matrix can be used to develop the multi-beam antenna systems. In this project, 1x4 leaky wave antenna elements will be integrated with 4x4 multilayered substrate integrated waveguide (SIW) Butler matrix for 2-D beam‐forming system at the Ka-band for 5G/connectivity applications and the proposed low‐cost SIW-based 2-D beam scanning antenna system is designed and simulated. In the proposed system, the SIW-based Butler matrix integrated with SIW-based leaky-wave antenna elements will be designed to generate the 2-D beam scanning.